Development and validation of I x V curve tracer for photovoltaic modules - MÃrcio Leal Macedo Luna (2016)
The IxV curves tracers for PV modules are used as a method of diagnosis of problems such as shadowing, faulty connections and degradation conditions. There are several types and brands tracers commercially available, but their costs are quite high in the Brazilian market due to the need to import. This thesis describes the development and validation of a IxV curve tracer for PV modules based on the electronic load method using MOSFET as load to the module. By appropriate variation of the MOSFET gate-source voltage signal was possible to acquire the points of voltage and current of the PV modules terminals. These points were recorded using a data acquisition board with PIC18F2550, which is controlled by a computer via a USB with a graphical interface to the user. This interface was developed in MATLAB software ensuring greater flexibility and functionality to the device. For PV module temperature measurements PT100 sensors were used and measurements of solar irradiance was used a pyranometer LP02 model Hukseflux Thermal Sensor manufacturer, these sensors were connected to a supervisory system consists of a PC and a programmable logic controller (PLC). The validation process was conducted by comparing the electrical parameters provided by the developed tracer and the commercial tracer MINI-KLA. From this comparison an error was generated for each parameter. Three PV modules of different electrical characteristics (20 Wp, 87 Wp e 160 Wp) were used and there was similarity between the curves of the developed tracer with the curves of the commercial tracer. The average of errors of the electrical parameters for the 3 PV modules was less than 5% at no shading conditions. In two conditions of shading, the IxV curves provided by the two tracers for the KC 85 T PV module were compared and it was observed in the first situation that the MINI-KLA tracer could characterize only partially the curve while the tracer developed could characterize the curve fully, in the second situation there was great similarity between the curves of the two tracers with maximum percentage difference in the electrical parameters equal to 5.41%.